2018
DOI: 10.1590/rbz4720170310
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of Amiata donkey through Multivariate analyses

Abstract: The objective of this study was to evaluate the morphology and biometrics of female Amiata donkeys reared in four different areas of southern Tuscany, Italy, to determine the differentiation degree of animals. Four southern Tuscan areas were investigated: two mountainous zones (East and West Amiata) and two flatter areas (Coastal area and Siena surrounding). Morphology and biometrics of adult female Amiata donkeys were collected to determine the homogeneity of the population. Primitive coat markings typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
(17 reference statements)
5
9
1
Order By: Relevance
“…Thus, we support the previous findings of Stanisic et al (2017) that the Banat donkey differs genetically from the Balkan donkey, and that it may be acknowledged as a distinct donkey breed in Serbia, the Balkans and worldwide (Alderson, 2003). A group of seven Banat donkey females represents a good core population which can be enlarged by introduction of unrelated individuals, both females and males, required for maintaining high levels of genetic diversity donkey, the Amiata donkey (Sargentini et al, 2009;Sargentini et al, 2018) and the Somali wild donkeys (Groves, 1986;Moehlman, 2002) may imply their common origin.…”
Section: Genetic Characterization Of the Banat Donkeysupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, we support the previous findings of Stanisic et al (2017) that the Banat donkey differs genetically from the Balkan donkey, and that it may be acknowledged as a distinct donkey breed in Serbia, the Balkans and worldwide (Alderson, 2003). A group of seven Banat donkey females represents a good core population which can be enlarged by introduction of unrelated individuals, both females and males, required for maintaining high levels of genetic diversity donkey, the Amiata donkey (Sargentini et al, 2009;Sargentini et al, 2018) and the Somali wild donkeys (Groves, 1986;Moehlman, 2002) may imply their common origin.…”
Section: Genetic Characterization Of the Banat Donkeysupporting
confidence: 90%
“…We also found that the classification accuracy in the Stepwise Forward Discriminant Analysis obtained with the model that included all studied morphological traits may also be achieved by applying the model that includes only four traits: hip height, croup width, body length and chest depth. These results highlight the redundancy of the majority of morphological traits used in our study, which are, more or less, similar to those commonly used for morphological characterization of donkey breeds (e.g., Folch & Jordana, 1997;Sargentini et al, 2009;Sargentini et al, 2018;Kefena et al, 2011;Kosuková et al, 2015;Labbaci et al, 2018;Ayad et al, 2019). Nonetheless, an important finding is that hip height/chest depth, croup width and body length are weakly correlated because these parameters (or parameters with which they are highly correlated) belong to different PCA-groups (Table S1).…”
Section: Morphological Characterization Of the Banat Donkeysupporting
confidence: 77%
See 3 more Smart Citations